2017
DOI: 10.15294/jda.v9i2.11991
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tax Amnesty Benefit Perception to Taxpayer Compliance

Abstract: This study aims to examine the effect of tax amnesty benefits perceived on This study aims to examine the effect of tax amnesty on taxpayer compliance on service quality as a moderating variable. The population in this study is the people who follow the tax amnesty in Surabaya is 58,415 individual taxpayers registered in KPP Pratama Surabaya. The sampling technique chosen was judgmental sampling with slovin formula obtained 100 samples. This study was analyzed using partial least square with path analysis mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
6
2
1
Order By: Relevance
“…The study of Sari & Nuswantara (2017) examined the effects of perceived benefits of tax amnesty and tax amnesty on taxpayer compliance. The results of this study showed that the benefits of tax amnesty were perceived to affect tax compliance that the quality of service cannot moderate the relationship between the two.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study of Sari & Nuswantara (2017) examined the effects of perceived benefits of tax amnesty and tax amnesty on taxpayer compliance. The results of this study showed that the benefits of tax amnesty were perceived to affect tax compliance that the quality of service cannot moderate the relationship between the two.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, tax amnesty is a policy that is often applied by many countries, including Indonesia (Said, 2017). Through the tax amnesty, it is hoped that MSME actors can increase their compliance with taxpayers (Sari & Nuswantara, 2017). Given that the tax amnesty program, in addition to increasing state revenue, also has the aim of increasing tax compliance and to improve a better tax base in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…There are three objectives that are targets for implementing tax amnesty in Indonesia (Sari & Nuswantara, 2017). First, increasing domestic liquidity, lowering interest rates and investment and improving the rupiah exchange rate through the transfer of assets.…”
Section: Introductionmentioning
confidence: 99%
“…Compliance with taxpayers in paying taxes can ensure state revenues to maintain the continuity of revenues from the sector. Compliance with taxpayers is very important because Indonesia adheres to a Self Assessment System (Sari & Nuswantara, 2017). Finance Minister Sri Mulyani Indrawati has formed a special tax reform team to improve taxpayer compliance, one of the efforts to improve taxpayer compliance is the implementation of the Tax Amnesty policy.…”
Section: Introductionmentioning
confidence: 99%